THE DISPERSION OF JUSTICE AND CRIMINAL PROCEDURAL LAW – SERBIAN STANDPOINT - Đurđić, Vojislav D; Davidov, Isak (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
At the moment when the carpet of traditional values draws beneath the bubbling energies of a new approach to the present and the future, the basic proposition of this paper is the thesis which claims that disregard for baselessness allows the existence of modern criminal proceedings. In order to elaborate on this claim, the authors describe a “grand stage” and list factors that have decisively influenced the change of the procedural paradigm. In their view, the rejection of a traditional view of the proceedings is only a reflection of wider social movements and ideas coming from other social sciences. The most traumatic episode in its development, caused by the transformation of the notion of the legitimacy of decisions, in the absence of the right solutions, the proceedings tried to overcome by simulation: the meaning of the postmodern proceedings is reduced to the imitation of the search for justice serving the stability of the system. Furthermore, the authors warn, this is no procedure of rationalization of criminal proceedings but its vulgarization. Even sadder, in their view, is the fact that vulgarization is represented as great progress. Aware that behind the intoxicating breath of illusion there will inevitably start to peep through the crisis of sense, the authors strive to, by moving the boundaries of the view “based on what is possible”, anticipate the crises and create far-reaching visions of the future of criminal proceedings. Clearly realizing that new views of the law have their ridges as well, they recommend keeping lit the icon lamp of the original understanding of justice and criminal proceedings as the instrument for reaching justice.